PENGARUH KOMPETENSI DAN KOMITMEN ORGANISASI TERHADAP EFEKTIVITAS KERJA KARYAWAN LPD DI KECAMATAN MENGWI - Putu Agus Eka Rismawan; I Gede Rihayana; I Wayan Gede Antok Setiawan Jodi (STIMI Handayani Denpasar, 2020)
This study aims to examine and analyze the influence of competency and organizational commitment on employee work effectiveness. This research was conducted at LPD Mengwi with used as a sample of 50 respondents. All data obtained from the distribution of questionnaires are feasible, then analyzed using SPSS 19.0. The results of the study give the meaning that competence has a positive and significant effect on employee work effectiveness and organizational commitment has a positive and significant effect on employee work effectiveness. The results of the beta regression coefficient or independent variable that have the most dominant effect on the dependent variable are organizational commitment variables. The data analysis technique used to answer the hypothesis of this study is multiple linear regression analysis, and the results of this study indicate that for competence shows a positive, it can be concluded that competence has a positive and significant effect on work effectiveness and for commitment organization shows a positive. Then it can be concluded that organizational commitment has a positive and significant effect on work effectiveness.